Effect of Diets Containing Treated and Untreated Sweet Orange (Citrus sinensis) Peels on the Performance and Nutrient Digestibility of West African Dwarf (WAD) Goats Fed Gamba Grass - Oloche, J.; Ameh, E.I.; Inalegwu, F. (Pakistan Journal of Nutrition, 2018)
Background and Objective: Feed shortage has been a major constraint to goat production in Nigeria particularly during the long dry season, thus supplementation to maintain animal weight during this period is required. Sweet orange peels are available all through the year and are reported to have calorie and protein values comparable with those of maize. Unprocessed sweet orange peels has been used in the diets of goats up to 50% level with no adverse effects. This study was, therefore, designed to evaluate the effects of diets containing treated and untreated sweet orange (Citrus sinensis) peels on the performance and nutrient digestibility of West African dwarf goats fed gamba grass. Materials and Methods: Nine male West African dwarf (WAD) goats aged 7-9 months with an average weight of 9.60 kg were used to evaluate the effect of diets containing treated and untreated sweet orange (Citrus sinensis) peels on the performance and nutrient digestibility of WAD goats fed gamba grass. Three diets, T1, T2 and T3 were formulated to contain 0% sweet orange peel meal (SOPM), 60% unfermented sweet orange peel meal (UFSOPM) and 60% fermented sweet orange peel meal (FSOPM), respectively and used as concentrate diets. The goats were randomly assigned to the diets in a completely randomized design (n = 3). Each goat was fed 200 g/day of the respective diet as supplement to gamba grass for a period of 77 days. Results: Results showed that there were no significant differences (p>0.05) among the treatments in all the performance parameters measured. The mean daily feed intake were 312.40, 297.70 and 312.50 g while the mean daily weight gain were 23.00, 16.96 and 14.59 g for T1, T2 and T3, respectively. The dry matter (DM), nutrient digestibility and nutrient intake values were also not significantly different (p>0.05) among the treatments. Dry matter and all the proximate constituents showed similar trend of slight decrease in digestibility from T1-T3. The nutrient intake also followed a similar trend as the DM and nutrient digestibility. Conclusion: Treated or untreated sweet orange peels can be used to replace 60% of maize offal in concentrate supplement diets of West African dwarf goats.